Adoption of SITARI Technology in the Management of State Property at Sriwijaya University - Mandayuni, Inayati; Sobri, Kgs. Muhammad; Alfitri; Lionardo, Andries (Universitas Merdeka Malang, 2025)
This study analyzes the implementation of SITARI (State-Owned Assets Inventory Information System) at Universitas Sriwijaya using the Technology, Organization, and Environment (TOE) framework. The research employs a qualitative descriptive method through interviews with 30 informants, including the rector, vice rectors, deans, vice deans, bureau heads, BMN coordinators, and SITARI operators. Informants were selected using purposive sampling. Data collection also included documentation and observation. The results show that adequate technological infrastructure, human resource competencies, and institutional support are key determinants of successful implementation. Persisting challenges involve inter-system integration, flexibility in data management, and internet network quality. These findings reinforce the literature on the benefits of e-government in public sector governance in higher education and underscore the importance of technological, organizational, and environmental factors in system adoption. Recommendations include developing a mobile-based application, strengthening security features, and providing user training. The study contributes theoretically to TOE-based technology adoption research and offers practical implications for universities seeking to enhance the effectiveness, transparency, and accountability of State-Owned Assets (BMN) management.